2015
DOI: 10.3389/fpsyg.2015.01403
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of vision and haptics to reaching and grasping

Abstract: This review aims to provide a comprehensive outlook on the sensory (visual and haptic) contributions to reaching and grasping. The focus is on studies in developing children, normal, and neuropsychological populations, and in sensory-deprived individuals. Studies have suggested a right-hand/left-hemisphere specialization for visually guided grasping and a left-hand/right-hemisphere specialization for haptically guided object recognition. This poses the interesting possibility that when vision is not available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 301 publications
(458 reference statements)
0
21
0
1
Order By: Relevance
“…It could be argued that, based on previous studies of left-handers, detection performance should be equally (rather than more) proficient, for leftward- versus rightward-oriented handles. There is some speculation, however, about the extent to which handedness is linked to manual grasping preferences (Stone & Gonzalez, 2015). For example, numerous studies have found that left-handers show either no hand preference, or sometimes a right-hand preference, for grasping (Gallivan et al, 2011; Gonzalez et al, 2006; Gonzalez & Goodale, 2009; Gonzalez et al, 2007; Main & Carey, 2014) –although it is unclear to what extent these results reflect a dominant role of the left-hemisphere in visuomotor control (Frey, Funnell, Gerry, & Gazzaniga, 2005; Goodale, 1988), versus the influence of long-term environmental pressures on left-handers.…”
Section: Resultsmentioning
confidence: 99%
“…It could be argued that, based on previous studies of left-handers, detection performance should be equally (rather than more) proficient, for leftward- versus rightward-oriented handles. There is some speculation, however, about the extent to which handedness is linked to manual grasping preferences (Stone & Gonzalez, 2015). For example, numerous studies have found that left-handers show either no hand preference, or sometimes a right-hand preference, for grasping (Gallivan et al, 2011; Gonzalez et al, 2006; Gonzalez & Goodale, 2009; Gonzalez et al, 2007; Main & Carey, 2014) –although it is unclear to what extent these results reflect a dominant role of the left-hemisphere in visuomotor control (Frey, Funnell, Gerry, & Gazzaniga, 2005; Goodale, 1988), versus the influence of long-term environmental pressures on left-handers.…”
Section: Resultsmentioning
confidence: 99%
“…While the importance of vision for action planning and execution has long been recognized (Helmholtz, 1867/1962 ), the role of the haptic sense for critical daily interactions with objects has received considerably less attention. While this gap has been recently narrowed (Dijkerman and de Haan, 2007 ) and more ecologically valid paradigms are being used and considered (Stone and Gonzalez, 2015 ), there is still a substantial work to be done in the domain of tactile processing and haptic perception (cf. Snow et al, 2015 ), as well as in the area of haptically-guided actions.…”
Section: Resultsmentioning
confidence: 99%
“…Ungerleider and Mishkin, 1982 ). Of course, purely sensorimotor and/or kinesthetic information (e.g., Fiehler et al, 2008 ) must be also incorporated in the functioning of the dorsal action stream (Goodale and Milner, 1992 ) for the guidance of such motor skills (For a recent review on the contributions of visual and haptic information to reaching and grasping see Stone and Gonzalez, 2015 ; see also a review on somatosensory processes involved in perception and action by Dijkerman and de Haan, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral sensory feedback plays a crucial role in the correct execution of a voluntary movement (Nowak et al, 2003, 2004; Weiss et al, 2011; Stone and Gonzalez, 2015). A continuously updated cyclic sensorimotor integration process is required to successfully complete a motor task.…”
Section: Introductionmentioning
confidence: 99%